Rediscovery of Cinnamomum travancoricum Gamble (Lauraceae) from the Southern Western Ghats, India - Geetha Kumary, M. P.; Pandurangan, A. G.; Santosh Kumar, E. S. (Journal of the Bombay Natural History Society (JBNHS), 2013)
No Abstract.